Development of agricultural production in Ukraine - Sauhina, Elena (My University, 2014)
Ukraine has enormous polential for the development of agricultural productivity due to favorable natural condilions: fertile black rich soil, and a very favorable climate condilions on the most of the country's territory. Ukraine was always known as one of the biggest importer of agricultural products in the world. But currently, the economy of Ukraine, and especially its agriculture, is in a period of stagnation. That's why there is the question if Ukrainian agriculture is able to provide enough agricultural production and to become an important exporter of agro-food products on a global scale.
Keywords: agricultural production; Ukraine; development; сільськогосподарське виробництво; Україна; розвиток; сельскохозяйственное производство; развитие